PROMOTING GENDER EQUALITY: PERSPECTIVES ON WOMEN'S RIGHTS AND ISLAMIC LAW IN SOUTHEAST ASIA - Novianty Djafri; Syarifuddin; Karman; Rosijanih Arbie; Muhammad Hero Soepeno (ADISAM Publisher, 2024)
This research paper explores the perspectives on promoting gender equality within the context of women's rights and Islamic law in Southeast Asia. The study adopts a qualitative approach, employing a comprehensive analysis of existing literature, scholarly works, legal documents, reports, and case studies to gain in- depth insights into the topic. The research begins with an overview of Islamic law in Southeast Asia, including its diverse interpretations and influence on family, Marriage, and inheritance matters. It then delves into understanding fundamental principles and practices related to women's rights within Islamic law, examining both supportive and discriminatory aspects. This research explores two main perspectives: liberal interpretations and feminist perspectives. Liberal interpretations advocate for gender equality within Islamic legal frameworks, analyzing progressive interpretations and reforms that promote women's rights. Case studies of countries or regions implementing inclusive approaches are examined to provide practical insights. Feminist perspectives critique patriarchal interpretations of Islamic law, conducting a feminist analysis of gender biases and discrimination within Islamic legal frameworks. The research explores feminist movements advocating for women's rights within the context of Islamic law, highlighting their efforts to challenge patriarchal norms and promote inclusive understandings of Islam. The research methodology involves a qualitative research design, including a literature review and data collection through interviews, focus group discussions, and surveys with relevant stakeholders. Thematic analysis will be conducted to identify common themes and perspectives, providing a comprehensive understanding of the different viewpoints on promoting gender equality within the framework of Islamic law in Southeast Asia.